Calligraphy Text Types Recognition Using Learning Vector Quantization - Mhd Furqan; Abdul Halim Hasugian; Ziqra Addilah (Yayasan Literasi Sains Indonesia, 2022)
Calligraphy is the art of beautiful writing. The term calligraphy comes from simplified English (calligraphy) taken from the Latin word